Kebebasan dan Etika Jurnalisme: Antara Propaganda Kepentingan dan Perlawanan Wartawan - Muslih Aris Handayani (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2008)
Both independence and ethics are two elements which determine the image and morals of journalism. The more highly they are respected, the healthier the press will be. Independent press is one which can present news and information which are true as it is found in reality. Independent press is not influenced by any intervention and is free from individual or group's interest. An honest and fair press presents an incident as it is for the shake of people's need.